2020
DOI: 10.3390/ijerph17113831
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Chronic Fatigue to Psychosocial Status and Quality of Life in Spanish Women Diagnosed with Endometriosis

Abstract: Aim: To analyze the levels of chronic fatigue in Spanish women with endometriosis and its relationship with their psychosocial status and quality of life (QoL). Methods: A total of 230 Spanish women with a clinical diagnosis of endometriosis were recruited. Chronic fatigue (Piper Fatigue Scale) and pelvic pain (Numeric Rating Scale) were evaluated. An on-line battery of validated scales was used to assess psychosocial status [Hospital Anxiety and Depression Scale, Scale for Mood Assessment, Pain Catastrophizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 77 publications
1
22
0
Order By: Relevance
“…Res. Public Health 2021, 18, 8177 2 of 13 demonstrated [10,11]. The most common symptoms of the disease include dysmenorrhea (60-80%), chronic pelvic pain (30-50%), infertility (30-40%), and dyspareunia (25-40%) [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Res. Public Health 2021, 18, 8177 2 of 13 demonstrated [10,11]. The most common symptoms of the disease include dysmenorrhea (60-80%), chronic pelvic pain (30-50%), infertility (30-40%), and dyspareunia (25-40%) [12].…”
Section: Introductionmentioning
confidence: 99%
“…This applies especially to uncertainty regarding the pathogenesis, heterogeneity of the course of the disorder, or its symptoms, which are often confused with other mental or physical disorders. Due to the aforementioned factors, the diagnosis of endometriosis is often overlooked, which is a serious social problem [12,18,19]. Treatment based on pharmacological methods relieves the symptoms of the disease but may involve the occurrence of side effects and a recurrence of symptoms after discontinuation of use.…”
Section: Introductionmentioning
confidence: 99%
“…For the comparison of patient groups, different types of methods were used. Twenty-one studies inves-tigated anxiety and depression symptoms in endometriosis patients without including a control group [27,33,34,36,37,[39][40][41][42]45,47,49,50,52,58,59,63,65,66,69,70,72,73]. Twenty-six studies compared endometriosis patients with a group of either healthy controls [30,32,35,38,39,46,51,55], CPP patients without endometriosis [29,48,54,60,67], infertile patients without endometriosis [61,64] or a combination of control groups [28,43,44,53,56,57,62,68,71].…”
Section: Study Subjectsmentioning
confidence: 99%
“…Studies that investigated other factors than pain or infertility, reported that higher scores of depression or anxiety in endometriosis patients were correlated to poorer quality of sleep [27], fatigue [52], poorer quality of life [32,49,50,52], gastrointestinal symptoms [70], lower self-esteem [36], lower emotional self-efficacy [36], lower sexual functioning [32,51], dysfunction on social adjustment [54], pain imagery [42] and clinical signs of pain sensitization [68]. In addition, it was reported that patients who used positive coping strategies had less depression [33,34].…”
Section: Correlating Factors With Depression and Anxiety In Endometriosis Patientsmentioning
confidence: 99%
“…Women are the main recipients of health programs on sexual and reproductive health. They may suffer from chronic diseases, such as endometriosis, which causes chronic fatigue, a worse quality of life, greater anxiety, and worse sleep, among other consequences, as Mundo-López et al [ 12 ] show. On the other hand, clinical and educational practices during pregnancy and childbirth influence the health status of women.…”
mentioning
confidence: 99%